Macronutrients and dissolved iron in a land-ocean approach: Influences of contamination by ore tailings in Southeastern Brazil - Cagnin, Renata Caiado; Longhini, Cybelle Menolli; Costa, Eduardo Schettini; da Silva, Cesar Alexandro; Zorzal-Almeida, Stéfano; Mendes, Danniel; Pasa, Vânya Márcia Duarte; Barbeira, Paulo Jorge Sanches; Delazari-Barroso, Alessandra; Gücker, Björn; Boëchat, Iola Gonçalves; Lima, Ana Teresa; et al. (Frontiers in Marine Science, 2022)
Recently, many dam rupture disasters related to the mining industry have caused significant disruption to ecosystems globally. Contaminants, including nutrients in excess, can be transported from the river basins to the ocean in great quantities. In 2015, millions of m3 of iron ore tailings were released in the Doce River basin in southeastern Brazil, leading to several damages to the river and marine ecosystem. So far, few studies have integrated the impact of these tailings on the river and the sea simultaneously. This research aims to provide a perspective on the macronutrients and iron concentrations and balance concerning the Doce River-sea continuum, the abiotic factors and phytoplankton response under a new steady state of iron enrichement environment. The ore tailings increased the concentrations of nutrients in the river and on the continental shelf, especially for dissolved silica and iron. There was also a long-term indirect enrichment of phosphorus due to adsorption onto Fe-oxides and of nitrogen due to the possible increase in N-fixing enhanced by the iron. N fixation/remineralization predominates in the river basin, while in the sea the hydrodynamics provides nutrients supply by the river and recycling from sediment resuspension. Nutrient ratios show DIP limitation in the river, while the complex marine environment brings both limitations on DIN, DIP, and DSi, as well as a stoichiometric equilibrium to the dataset. The phytoplankton response to the abiotic factors was more representative in the river basin than at the continental shelf. This work emphasizes the importance of reporting local data for understanding global land-ocean nutrient fluxes and their potential influence on primary productivity and trophic chain balance.